The Implications of HIV/AIDS on Tourism Enterprises in the Sub-Saharan Africa - KETSHABILE , Lisbon Simeon (Asian Journal of Empirical Research, 2013)
Tourism plays a vital role in the economy of many countries in the Southern African Region. It creates employment, earns foreign exchange, markets the Southern African countries globally, attracts foreign investments and contributes to Gross Domestic Products (GDP). The paper analyses the potential of tourism entrepreneurship in alleviating poverty in Botswana in an innovative approach, contributing to the understanding of relationship between poverty and HIV/AIDS and the implications of HIV/AIDS on tourism entrepreneurship as well as recommending strategies that can be applied in maximising tourism benefits and mitigating the negative impacts of HIV/AIDS on the tourism sector. This paper is useful for tourism businesses, tourism policy makers, decision makers and tourism leaders, government officials and general communities in realising that they can best utilise tourism to fight the spread HIV/AIDS. This also helps tourism role players to work closely with the communities in developing tourism for the benefits of the economy of the Southern African tourism and communities in general. This paper should be of value to academics who wish to increase their knowledge of the HIV/AIDS implication on the tourism businesses.